Effective supply chain in ready made garments in Bangladesh: study on Alfa Fashion - Rahman, Muhammad Taslim (BRAC Univerisity, 2017)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2017.